TB specific intracellular cytokines production in Synovial liquid for diagnosis of tuberculous arthritis - Serena Vita; Claudia Mascia; Blerta Kertusha; Raffaella Marocco; Ilaria Sauzullo; Fabio Mengoni; Irene Pozzetto; Alessandro Scalzi; Parni Nijhawan; Stefano Savinelli; Laura Fondaco; Anna Carraro; et al. (Journal of Infection in Developing Countries)
Introduction: Skeletal tuberculosis (TB) accounts for about 10 to 35% of extrapulmonary cases and the knee is the most frequent site after the spine and hip. The diagnosis is difficult and largely clinical.